2006
DOI: 10.1104/pp.106.092742
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Functional Validation of Genes Involved in Reproductive Stages of Orchids

Abstract: Plants in the largest family of angiosperms, Orchidaceae, are diverse in both specialized pollination and ecological strategies and provide a rich source for investigating evolutionary relationships and developmental biology. However, studies in orchids have been hindered by several challenges that include low transformation efficiency and long regeneration time. To overcome such obstacles, we selected a symptomless cymbidium mosaic virus (CymMV) isolate for constructing virus-induced gene-silencing vectors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 42 publications
0
65
0
1
Order By: Relevance
“…The expression of PaPTP1 gene is mainly localized in floral organs and in response to wounding. Generation of loss-of-function orchid plants by virus-induced gene silencing has been described and achievable (Lu et al 2007). Further functional analysis using PaPTP1-silenced orchid plants should provide novel information on the role of reversible tyrosine phosphorylation in developmental biology and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PaPTP1 gene is mainly localized in floral organs and in response to wounding. Generation of loss-of-function orchid plants by virus-induced gene silencing has been described and achievable (Lu et al 2007). Further functional analysis using PaPTP1-silenced orchid plants should provide novel information on the role of reversible tyrosine phosphorylation in developmental biology and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, concerning GLO-like genes except higher eudicots, there have also been reports using virus-induced gene silencing. For example, AqvPI in Aquilegia (Kramer et al 2007) and PeMADS6 in Phalaenopsis (Lu et al 2007), which showed that petaloid organs changed to sepaloid organs upon down-regulation of these class B genes. With regard to the DEF-like genes, it has been reported that in the superwoman mutant of rice and the silky1 mutant of maize, lodicules, which are considered to correspond to petals, change to palea or lemma-like organs and stamens change to carpels (Nagasawa et al 2003, Ambrose et al 2000.…”
Section: Consideration Of Amino Acid Sequencesmentioning
confidence: 99%
“…Six different viruses have been developed into viral vectors for VIGS applications in monocots to date: Barley stripe mosaic virus (Scofield et al, 2005), Brome mosaic virus (BMV; Ding et al, 2006), Cymbidium mosaic virus (Lu et al, 2007), Rice tungro bacilliform virus (Purkayastha et al, 2010), Bamboo mosaic virus together with its associated satellite RNA (Liou et al, 2014), and, most recently, Cucumber mosaic virus (CMV; Wang et al, 2016). Among these, the BMV and CMV vectors have the ability to infect and induce gene silencing in maize (Zea mays; Ding et al, 2006;Lee et al, 2015;Wang et al, 2016).…”
mentioning
confidence: 99%